Global prevalence and risk factors of equine infectious anemia: A systematic review and meta-analysis - Lintang Winantya Firdausy; Faisal Fikri; Arya Pradana Wicaksono; Hakan Çalışkan; Muhammad Thohawi Elziyad Purnama (Veterinary World)
Background and Aim: Equine infectious anemia (EIA) is a lentiviral disease affecting members of the Equidae family, with global distribution and significant implications for animal health and biosecurity. Despite numerous individual reports, a comprehensive synthesis of its global prevalence and risk factors remains lacking. This study aimed to conduct a systematic review and meta-analysis to estimate the global prevalence of EIA, identify diagnostic trends, and evaluate factors associated with heterogeneity across studies.